p53 expression during normal tissue regeneration in response to acute cutaneous injury in swine. - Antoniades, H N (1994)
The present studies investigated the in vivo expression of the p53 suppressor gene and protein product in response to acute cutaneous injury in swine, along with the parallel expression of the c-sis/PDGF-B mitogen and its receptor beta (PDGF-R beta). p53 expression was shown to be suppressed during the period of active cellular proliferation in the injured tissue and to reemerge during the stages of healing. In contrast, c-sis/PDGF-B and PDGF-R beta were expressed during the early phase of active cellular proliferation and they were suppressed upon healing. This inverse relationship between mitogenic growth factors and p53 suggests the presence of well-controlled physiologic mechanisms that regulate in vivo the processes of normal tissue repair in response to injury. At the stages of tissue regeneration, these mechanisms include both the expression of growth factors that promote cell proliferation and the suppression of p53 that downregulates proliferation. At the stages of healing, the expression of the mitogenic growth factors is suppressed and that of p53 reemerges, reaching its peak at the time of complete epithelialization and healing of the injured tissue. These studies are the first to link the response of p53 protein to physiologic processes of tissue regeneration in vivo.